2019
DOI: 10.1186/s40554-019-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing texts: a tool for generating thematic-progression diagrams

Abstract: The Hallidayan Theme-Rheme framework has been extensively applied in corpusbased studies over the years, offering valuable insights into the use and choice of Themes in news articles (Liu and Tucker 2015, Rahnemoon et al. 2017), student

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The studies found that the field of the speech texts mostly show the action employed by both speaker and audience. Other studies emphasized the textual function of the text (Ahmed & Al, 2020;Briones, 2016;Leong, 2019;Ong, 2019;Othman, 2020;Potter, 2016;Suparto, 2018). They highlighted that as one of the meta-functions of language, the textual function of the text which is realized by register category of mode was of benefit to deliver the message of the text.…”
Section: Introductionmentioning
confidence: 99%
“…The studies found that the field of the speech texts mostly show the action employed by both speaker and audience. Other studies emphasized the textual function of the text (Ahmed & Al, 2020;Briones, 2016;Leong, 2019;Ong, 2019;Othman, 2020;Potter, 2016;Suparto, 2018). They highlighted that as one of the meta-functions of language, the textual function of the text which is realized by register category of mode was of benefit to deliver the message of the text.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that not only scientists of the previous centuries, but also modern linguists have paid attention to the study of the actual division of a sentence or utterance. The role of the actual sentence division for the methodology of teaching a foreign language is emphasized in recent works of such linguists as Alyousef (2016), Chen et al (2011), Leong (2019), Potter (2016), Wei (2016).…”
Section: Problem Statementmentioning
confidence: 99%
“…Other studies highlighted the textual meaning of the text (Ahmed & Al, 2020;Briones, 2016;Leong, 2019;Ong, 2019;Othman, 2020;Potter, 2016;Suparto, 2018). They revealed that textual meaning can be revealed by deeply looking the theme and rhyme of the text.…”
Section: Introductionmentioning
confidence: 99%